ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9415123
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Morphological Neural Networks: Training, Pruning and Enforcing Shape Constraints

Abstract: In this paper, we study an emerging class of neural networks, the Morphological Neural networks, from some modern perspectives. Our approach utilizes ideas from tropical geometry and mathematical morphology. First, we state the training of a binary morphological classifier as a Difference-of-Convex optimization problem and extend this method to multiclass tasks. We then focus on general morphological networks trained with gradient descent variants and show, quantitatively via pruning schemes as well as qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Dimitriades and Maragos investigated the use of purely morphological architectures in computer vision classification and found that these models performed slightly worse than their convolutional counterparts [29]. This has led to an increase in the use of hybrid morphological-convolution network architectures in various domains [28,[30][31][32][33][34].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimitriades and Maragos investigated the use of purely morphological architectures in computer vision classification and found that these models performed slightly worse than their convolutional counterparts [29]. This has led to an increase in the use of hybrid morphological-convolution network architectures in various domains [28,[30][31][32][33][34].…”
Section: Related Workmentioning
confidence: 99%
“…This has led to an increase in the use of hybrid morphological-convolution network architectures in various domains [28,[30][31][32][33][34]. The sparsity induced by replacing linear operators (such as traditional 2D convolution) with morphological ones has been previously examined in the literature [22,29,35].…”
Section: Related Workmentioning
confidence: 99%